20. RESULTS OF LAPAROSCOPIC SURGERY FOR OVARIAN CYSTC IN PREGNANT WOMEN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of laparoscopic surgery for ovarian cysts in pregnant women at Nghe An Obstetrics and Pediatrics Hospital.Subjects and methods: A retrospective, cross-sectional study was conducted on 69 pregnant women with ovarian cysts who underwent laparoscopic surgery from June 2021 to June 2024.Results: 100% of patients have successful endoscopic surgery. There is no case of open surgery. The average age of the patient is 27.9 ± 4.8 years old. The most common gestational age is 13-18 weeks, the lowest is 7 weeks and the highest is 28 weeks. 97.1% of pregnant women are preserved ovarian. The ovarian tumor is concentrated mainly in the gestational age of less than 12 weeks (82.3%). All cases have no complications of miscarriage after surgery.Conclusion: Endoscopic surgery is an effective and safe method to treat ovarian tumors in pregnant women, often indicated for pregnancy from 13-18 weeks. However, with the advances of current laparoscopic surgery, the surgery is more widely available, which can be performed when the patient is very small as 7 weeks if twisted without affecting the fetus, also It can be done when the fetus has grown, specifically up to 28 weeks as in the study..
Keywords: Laparoscopic surgery; ovarian cysts; pregnant women